Comparative life cycle assessment of battery electric vehicles in developing countries under current and future electricity mix scenarios - Yash Aryan; Akhila C K; Anil Kumar Dikshit; Amar Mohan Shinde (Discover Sustainability)
Abstract Electric vehicles and renewable energy sources are crucial in advancing sustainable transportation systems in developing countries. The environmental performance of electric vehicles largely depends on the electricity mix used during their use phase. Given the evolving energy landscape in developing countries, a comprehensive and dynamic assessment is essential to provide precise insights for consumers and policymakers. Therefore, this study conducts a comparative life cycle assessment of battery electric vehicles (BEV) in the top 10 electric vehicle-selling developing countries for current (2023) and future (2030) electricity mix scenarios. The global warming potential was assessed for 150,000 vehicle km travelled (VKT) as a functional unit. The results indicate that Brazil consistently exhibits the lowest life cycle GWP impact of approximately 18,000 kg CO2-eq in both 2023 and 2030, mainly due to its high reliance on hydropower. Conversely, BEVs operating under South Africa’s 2023 electricity mix show the highest GWP impact (39320 kg CO2-eq), largely due to the country’s heavy dependence on coal-based power generation. In the 2030 electricity mix scenario, Malaysia emerges as the country with the highest GWP impact (29650 kg CO2-eq), followed closely by Indonesia (29300 kg CO2-eq). While Brazil has already met the global average GWP target of 130 g CO2-eq/VKT, only a few countries, such as India, Vietnam, and Turkey, are expected to approach this target. Eventually, the outcomes of the study will provide valuable insights for policymakers and stakeholders aiming to maximize the sustainability of electric mobility.